Unlocking Innovation in homestead farms: Exploring drivers and barriers to innovation adoption among farming households in Uzbekistan - Rajiv, Sharanya; Akramov, Kamiljon T.; Dhehibi, Boubaker (International Food Policy Research Institute, 2024)
Homestead, or tomorqa, farms play a key role in agriculture and food security in Uzbekistan. These small-scale farms are integral to the livelihoods of more than 5.5 million rural households, collectively utilizing over 500,000 hectares of agricultural land, which accounts for nearly 15 percent of the country’s total arable agricultural land area.1 The significance of homestead farms is also underscored by their substantial contribution to the overall agricultural output of the country, producing the majority of horticulture and livestock products. In 2023, homestead farms produced approximately 62 percent of agricultural products, 37 percent of crop output, and an impressive 88 percent of livestock production.